Brain contusion as the main risk factor of memory or emotional complaints in chronic complicated mild traumatic brain injury. (16th April 2017) - Su, Bei-Yi; Guo, Nai-Wen; Chen, Nan-Chun; Lin, Sheng-Sian; Chuang, Ming-Tsung; Liao, Yu-Chi; Kuo, Chia-Min; Lin, Cheng-Wei; Chou, Willy; Kuo, Jinn-Rung; Yen, Shih-Yin
ABSTRACT: Objective : To investigate the risk factors for memory or emotional complaints in patients with complicated mild traumatic brain injury (mTBI). Methods : Retrospective analysis of medical records was conducted by physicians in a teaching hospital in Southern Taiwan, and complicated mTBI had been identified by means of computed tomography. Psychological complaints, including problems with memory and emotions, were collected by structured telephone interviews, 10–15 minutes long, and were held with subjects who agreed to participate in our study. Among 327 patients who were injured for more than two years, 190 agreed to join this study (mean age: 41.6 years; male: 60.5%; stably employed: 50.0%). We used demographic data and neurological factors to predict memory or emotional complaints without muscle power or response speed (MEMR) complaints. Results : Only the presence or absence of cerebral contusions predicted memory or emotional complaints without MEMR complaints in different employed status, and the odds ratio was 4.82–13.50 times higher for those with cerebral contusions than for those without. Conclusions : Cerebral contusions were the primary risk factor for MEMR complaints in chronic complicated mTBI. Early preventive psychological intervention might be necessary for patients with complicated mTBI and cerebral contusions.